Cultural practices and values at the societal level in Estonia in comparison with neighbouring countries - Alas, Ruth; Tuulik, Krista (Journal of Business Economics and Management, 2007)
The research question in this paper involves comparing the differences between the actual regional societal culture (cultural practices) and the desired regional societal culture (cultural values) in Estonia with cultural practices in neighbouring countries Russia and Finland. Practices at the organization level are compared with practices and values at the societal level in Estonia. An analysis of results from the GLOBE research project have indicated that Russia and Finland have both had an impact on Estonian culture and practices. Similarities with Finland stem from the shared genetic background and appear in Estonian values. The Soviet heritage can be seen in Estonian societal and organizational practices, which are closer to Russian than Finnish indicators. Change in practices takes time and starts from within and among organizations, but over time this may also spread to the society. First Published Online: 14 Oct 2010